The Influence of Product Quality, Information Quality, and Consumer Trust on Boiler Machine Purchase Decisions (Case Study of CV. Jaya Makmur Sentosa, Tangerang City) - Laudya Putri Suwandi; Anna Sofia Atichasari; Sutarjo Sutarjo (Maneggio, 2025)
This study aims to analyze how product quality, information quality, and consumer trust influence boiler machine purchasing decisions. This study is a quantitative study using statistical data. The research population is consumers who have purchased boiler machines at CV. Jaya Makmur Sentosa. The study used a saturated sampling technique so that 60 respondents were obtained as a research sample. The data collection technique is primary data through a Likert scale questionnaire 1-5 distributed to respondents. While secondary data is in the form of previous literature studies. The data analysis technique in the study uses Smart-Pls in the form of the Partial Least Squares (PLS) Method. The results of the study show that Information Quality has a positive and significant effect on Purchasing Decisions. These results indicate that the strategy of developing the quality of information contained in the product, in this case the boiler machine as the object of research, makes a real contribution to increasing purchasing decisions. Meanwhile, the results of the study show that Product Quality and Consumer Trust have no positive and insignificant effect on Purchasing Decisions. This means that some consumers consider other factors, such as price, product quantity, customer satisfaction, and so on, when making a transaction.